Investigation of indoor positioning system using visible light communication - See, Yuen Chark (IEEE, 2017)
This paper investigates the use of Light Emitting Diode (LED) as Visible Light Communication (VLC) in Indoor Positioning System (IPS). A Visible Light Communication in Indoor Positioning System (VLC-IPS) is constructed and tested. The proposed system comprised of two components; transmitter and receiver. The transmitter consists of four LEDs. These LEDs are modulated to 1 kHz, 3 kHz, 5 kHz and 7 kHz Unique Frequency Identification (F-ID) respectively by using a timer. The receiver consists of a photodiode (PD) which controlled by an ARM Cortex M4 microcontroller. The microcontroller will perform Analogue Digital Conversion (ADC) and Fast Fourier Transform (FFT) on received analogue optical signal from the LEDs. Received Signal Strength (RSS) output of FFT are inserted into Lambertian optical wireless direct current (DC) gain and trilateration algorithms to calculate the distance and coordinate the photodiode receiver respectively relative to the LED transmitters. The average positioning error between the actual and estimated coordinate obtained from the proposed VLC-IPS design is 0.3941m, which is, within the remit of tolerable error.